Effect of chitosan-based edible coating on chemical and physical properties and quality of fruit: article - Zulkiflee, Nurul ‘Ain; Mohd Yusof, Noorsuhana; Jai, Junaidah (2017)
Foodborne outbreaks, precocious decaying and economic losses were common problems related to fresh fruit retention. These problems have led to the advance of novel technologies and systems for food protection such as edible coating based on natural compounds. In this study, an edible coating has been applied on the surface of fruits to lengthen its shelf-life. Other than that, it also offers protection against bacterial infection that leads to fruits spoilage by suppressing respiration, transpiration, and microbial growth. Latest studies have indicated chitosan as an effective coating that prolongs shelf-life and improves a storability of fresh fruit. Few characteristics possess by chitosan which makes it an excellent coating are high antimicrobial activity, biodegradability and non-toxic. The chitosan coating is also incorporated with turmeric essential oil as innovation based on the possible incorporation of the bioactive ingredient. The synergy between these two components may be useful to avoid a chain of biochemical and nutritional changes that could lead to fruits spoilage. The objectives of this study were to determine the effectiveness of chitosan-based edible coating in prolonging the quality of fruit and the effect of chitosan-based edible coating on chemical and physical properties of strawberry fruit from the chitosan-based formulation chosen. Fruits were dipped for 60 seconds in chitosan solution incorporated with turmeric essential oil. Non-treated fruits served as a control treatment. Samples were stored at room temperature up to 5 to 7 days. Quality analysis is performed every 2 days. The analysis included measurements of visual decay infection, structural analysis of chitosan-based solution, vitamin C determination and total soluble solid content (TSS). The results show that chitosan solution incorporated with turmeric essential oil could successfully improve shelf-life stability and retard postharvest deterioration of strawberries.